Association Between Antiretroviral Therapy Adherence and Viral Suppression Among People Living with HIV in Bogor City: A Case-Control Study - Ike Nurjana Tamrin; Arabia Tamrin (Media Kesehatan Politeknik Kesehatan Makassar, 2026)
Human Immunodeficiency Virus (HIV) continues to be a major global public health problem. HIV requires Antiretroviral (ARV) treatment to suppress the amount of HIV virus in the body. Adherence to ART can be influenced by a number of factors, including the patient's social situation and clinical condition, the prescribed regimen, and the patient-provider relationship. Adherence to ARV treatment is essential for PLWHA to achieve treatment success. Conversely, non-adherence to treatment can result in virologic failure. Virologic failure is an early sign of treatment failure. Over time, virologic failure will be followed by immunologic failure and ultimately clinical failure will occur. The purpose of this study was to determine the relationship between adherence to antiretroviral therapy and viral suppression in HIV patients in Bogor City. Research Methods This study is a quantitative study using an analytical observation method with a case-control study design. The study population was all people with HIV recorded in SIHA version 1.7 in Bogor City. The sampling technique used total sampling for the case group and simple random sampling for the control group. Data were taken from viral load examinations on a sample of 84 people and controls 3 times more than the number of cases, namely 252 people. The results of the study showed a significant relationship between adherence to antiretroviral therapy and viral suppression in HIV sufferers in Bogor City with a large association of 13.39 (95% CI: 6.09 - 29.41, p value: 0.000). Conclusion People with HIV in Bogor City who do not experience viral suppression have a low level of adherence with a proportion of 34.52% greater than in the group of people with HIV who experience viral suppression with a proportion of only 5.16% at the same level of adherence